THE ROLE OF KHURSHID DAVRON AND YASUSHI INOUE IN THE DEVELOPMENT OF UZBEK-JAPANESE LITERARY RELATIONS - Sattorova Gulmira Boburovna (International Journal of Literature and Language Studies, 2026)
Abstract: This article examines the role of Khurshid Davron and Yasushi Inoue in the development of Uzbek-Japanese literary relations from a comparative-literary perspective. The study focuses on historical memory, the image of Samarkand, the Silk Road motif, cultural dialogue and the artistic interpretation of Eastern civilization. Khurshid Davron is considered as an Uzbek writer who poetically reinterprets national identity and historical heritage, while Yasushi Inoue is analyzed as a Japanese author who created a philosophical and artistic image of Central Asia and the Western Regions. The article argues that the works of both writers function as important aesthetic and educational sources for deepening literary and cultural communication between Uzbekistan and Japan.